Analisis Pra Penerapan Sanitation Standard Operating Procedure (SSOP) Di Suis Butcher Steak House Setiabudhi Bandung - Noviani, Silvia; Sudono, Agus; Priatini, Woro (Universitas Pendidikan Indonesia, 2016)
Problems studied in this research is application of hygiene and sanitation atSuis Butcher Steak House Setiabudhi Bandung. This research is done based onsome guest comment from customer who comes to Suis Butcher Steak HouseSetiabudhi Bandung. This is cause of neglect of food handling that made byemploye. The purpose of this research is for analysis of pre application ofsanitation standard operating procedure (SSOP) at Suis Butcher Steak HouseSetiabudhi Bandung. Research method that used in this research is quantitativemethod with description and accumulation technique of data is field research(observation, interview, documentation, questionnaire) and literature researchstudi. Questionnaire had given to 26 employe at Suis Butcher Steak HouseSetiabudhi Bandung, in particular for food product and food service section.Analysis technique of data had done with validitas and reliabilitas experiment forÂ questionnaire that observe.Out of this analysis show that employeâ€™s knowledge of Sanitation StandardOperating Procedure is 75% and analysis condition of aspects SanitationStandard Operating Procedure that applied in di Suis Butcher Steak HouseSetiabudhi Bandung is 76.5%.Application of hygiene and sanitation with Sanitation Standard OperatingProcedure is one of the needed to apply at Suis Butcher Steak House SetiabudhiBandung. Sanitation Standard Operating Procedur is a way for prevent crosscontamination, keep cooking process and for apply principle of hygiene andsanitation.